2016
DOI: 10.1002/jmri.25496
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of fat content in vertebral marrow using a modified dixon sequence to differentiate benign from malignant processes

Abstract: 3 J. MAGN. RESON. IMAGING 2017;45:1534-1544.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 38 publications
(140 reference statements)
5
49
0
Order By: Relevance
“…129,130 It has also recently been shown that the fat fraction based on chemical-shift encoding-based water-fat imaging could be used to allow a distinction between benign and malignant causes of focal bone marrow abnormalities when difficulty in the qualitative interpretation of conventional MR image arises. 131 DIFFUSION. Diffusivity is reduced in tissue with a high cellularity, e.g.…”
Section: Metabolic Diseasesmentioning
confidence: 99%
“…129,130 It has also recently been shown that the fat fraction based on chemical-shift encoding-based water-fat imaging could be used to allow a distinction between benign and malignant causes of focal bone marrow abnormalities when difficulty in the qualitative interpretation of conventional MR image arises. 131 DIFFUSION. Diffusivity is reduced in tissue with a high cellularity, e.g.…”
Section: Metabolic Diseasesmentioning
confidence: 99%
“…THE PROPORTION of bone marrow adipose tissue is thought to be related to the strength and remodeling capacity of the bone, and quantitative changes in the bone marrow fat fraction have been examined in various pathologic states: first, bone marrow adiposity has been found to correlate with the bone loss pathophysiology in the course of osteoporosis and to increase the fracture risk in metabolic diseases such as diabetes mellitus . Second, bone marrow adipose tissue has been shown to be replaced by malignant bone marrow processes, potentially providing a diagnostic instrument for the differentiation of benign and malignant bone marrow lesions . Third, increased bone marrow fat fractions have been observed in patients with malignant disease and a positive treatment response to both chemotherapy and radiation .…”
mentioning
confidence: 99%
“…2 Second, bone marrow adipose tissue has been shown to be replaced by malignant bone marrow processes, potentially providing a diagnostic instrument for the differentiation of benign and malignant bone marrow lesions. [3][4][5] Third, increased bone marrow fat fractions have been observed in patients with malignant disease and a positive treatment response to both chemotherapy and radiation. [6][7][8] Therefore, bone marrow fat quantification holds considerable potential for diagnosing and monitoring of disease, and can help to provide further insight into bone pathology and its relation with bone marrow adipogenesis.…”
mentioning
confidence: 99%
“…In the post-processing of the in-phase and out-ofphase images, there is a step for water and fat separation, so that adding the in-phase and out-of-phase images results in a water image, while subtracting the out-of-phase image from the in-phase image gives a fat image (1) . Thus, the Dixon technique allows the measurement of the fatwater fraction in a region of interest larger than that achieved with spectroscopy and with higher spatial resolution (1,13,15,16) . In general, this concept could be used for the suppression or quantification of fat in various types of pulse sequences (14) .…”
Section: Basic Physical Principlesmentioning
confidence: 99%
“…Many variants of the Dixon technique have been developed, providing more consistent separation of fat and water signals, as well as allowing correction for many confounding factors (15) . The development of the technique has shown that symmetrically acquired echoes can produce artifacts that can degrade image quality.…”
Section: Basic Physical Principlesmentioning
confidence: 99%